Some fixed point theorems on α-β-G-complete G -metric spaces - Chary, V.S.; Reddy, G.S.M.; Isik, H.; Aydi, H.; Chary, D.S. (Carpathian Mathematical Publications, 2021)
In this manuscript, we initiate the concept of rectangular α-G-admissible mappings with respect to β and we consider related type contractions in the setting of G-metric spaces. We provide some fixed point results. Also, some examples are given to support the obtained results.